Time perception: A study of young Brazilian workers - Kely César Martins de Paiva; Cinthia Mara Oliveira e Souza (Tourism & Management Studies, 2016)
Given the importance of time as a category of analysis in organisational research, this study’s objective was to analyse the time perceptions of young Brazilian workers. The study was guided by the five time dimensions proposed by Bluedorn and Jaussi (2007): polychronicity, speed, punctuality, temporal depth and entrainment. The field work consisted of a descriptive case study, paired with a quantitative analysis of data collected with a structured, closed and self-administered questionnaire based on Paiva, Dutra, Santos and Barros’s (2013) Time Perception Scale. The data were analysed using univariate and bivariate statistics. Monochronic, slow and punctual behaviours, with past temporal depth, predominate among young workers. The results also show that respondents are highly temporally entrained from various perspectives, particularly entrainment through synchrony, followed by entrainment through leadership and conduction. Based on these findings, the contributions and limitations of the study are presented, and new possibilities for future research are suggested.